2002
DOI: 10.1152/ajpendo.00131.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 and CTGF are molecular markers of bladder wall remodeling after outlet obstruction

Abstract: Cysteine-rich protein (Cyr61) and connective tissue growth factor (CTGF) are key immediate early growth factors with functions in cell proliferation, differentiation, and extracellular matrix synthesis. Studies were performed to assess the gene expression profile of Cyr61 and CTGF in rat urinary bladder during growth in response to partial outlet obstruction. The mRNA levels of Cyr61 as determined by ribonuclease protection assay increased sharply after 1 day and remained elevated throughout the time period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Also, CCN1/ CYR61 was induced in proximal straight tubules following ischemic reperfusion injury of the kidney (35). In the obstructed bladder, expression of CCN2/CTGF and CCN1/CYR61 were also induced (36). Disruption of Hippo signaling following actin polymerization likely represents a general mechanism in regulating tissue damage and remodeling, linking mechanical alterations of structural components to intracellular signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Also, CCN1/ CYR61 was induced in proximal straight tubules following ischemic reperfusion injury of the kidney (35). In the obstructed bladder, expression of CCN2/CTGF and CCN1/CYR61 were also induced (36). Disruption of Hippo signaling following actin polymerization likely represents a general mechanism in regulating tissue damage and remodeling, linking mechanical alterations of structural components to intracellular signaling.…”
Section: Discussionmentioning
confidence: 95%
“…CCN1 was first linked to augmented mechanical stretch by the observation that its expression is up-regulated under pathophysiological conditions (e.g. after balloon angioplasty or outlet obstructed bladders (7,8,21).…”
Section: Discussionmentioning
confidence: 99%
“…They may involve matrix degradation, cell motility, angiogenesis, etc. CCN proteins could regulate biological processes such as angiogenesis, chondrogenesis, tumorigenesis, fibrotic and vascular diseases [4][5][6]40] . Numerous in vitro studies indicated that Cyr61 protein was related to angiogenesis [41] .…”
Section: Discussionmentioning
confidence: 99%